THE LITHUANIAN CONSTITUTIONAL ACTS OF NOVEMBER 2, 1918 AND OF APRIL 4, 1919 – TWO SEPARATE CONSTITUTIONS OR TWO VERSIONS OF THE SAME ACT? - Machovenko, Jevgenij (Teisė, 2017)
In the article genesis and contents of the Fundamental Principles of Temporary Constitution adopted by the Lithuanian State Council on November 2, 1918 and on April 4, 1919 are investigated. The author intends to find out what these documents there are – two temporary constitutions or two versions of the same constitutional act.